Latex allergy and occupational asthma in health care workers: adverse outcomes. - Amr, Sania (National Institute of Environmental Health Science, 2004)
The prevalence of natural rubber latex (NRL) allergy has been estimated to be 5-18% in health care workers, and latex exposure has been one of the leading causes of occupational asthma in the last several years. We present the cases of two nurses who developed sensitivity to NRL, both with dermatologic symptoms and respiratory symptoms that included asthma. They were referred to the University of Maryland for evaluation of their allergies, then for occupational and environmental consults. The patients' allergy to NRL was confirmed on the basis of clinical history, a positive skin test to latex, and the presence of latex-specific immunoglobulin E (IgE) serology by radioallergosorbent test (RAST). Both patients worked in the same community hospital for approximately 20 years; one was an endoscopy nurse and the other worked in the emergency department. Following the diagnosis of allergy to latex, both patients avoided direct skin contact with latex, but they continued to work in the same respective environments, where powdered latex gloves and other potentially sensitizing chemicals were used. Instead of improving, the clinical condition of the patients worsened and they remained symptomatic, even after they were removed from their workplace. Their airways reacted to low levels of a variety of sensitizers and irritants in the environment, and they became depressed. Both nurses were referred for vocational rehabilitation.